Fair not flat : how to make the tax system better and simpler - McCaffery, Edward J. (Chicago studies in ethnomusicology., 2002)
Everyone knows that the current tax system is unfair. Some of the richest people in America pay no tax, while a huge share of the tax burden falls on the rest of us. The tax code is far too complex, with volumes of rules that no ordinary person could possibly comprehend. Some conservatives have called for a so-called flat tax, but a flat tax is not necessarily simple, and "flat" means "more" for most taxpayers. McCaffery proposes to tax spending, not income and savings. Collected at its lower levels through a national sales tax, most people would not have to file a return. Necessities would be taxed less than ordinary and luxury items. A supplemental tax on spending for the wealthiest individuals would make the national sales tax progressive. No one would be taxed directly on savings.--From publisher description.